Denture Care Behavior and Lifespan of Removable Partial Dentures in Indonesian Military Personnel: An Approach Using the Theory of Planned Behavior - Handayani, Nining; Budiarto, Arief; Rachman, Arif; Setiawan, Arlette Suzy (European Journal of Dentistry, 2024)
Objectives In the context of military health, removable partial acrylic dentures (RPADs) are crucial for the quality of life and performance of Indonesian National Armed Forces (TNI) soldiers. Given the demanding and unpredictable military environment, RPADs provide a solution for soldiers experiencing tooth loss. This research aims to identify behavioral factors influencing the lifespan of RPADs among TNI soldiers.Materials and Methods This study employed an observational cross-sectional design with an analytical approach. The study population consisted of all patients fitted with RPADs at Ladokgi RE Martadinata from 2017 to 2019. The inclusion criteria included TNI soldiers using good functionality RPADs from 2017 to 2019. Data were collected through a valid questionnaire (Cronbach's alpha = 0.738) and analyzed using Spearman's rank correlation and multiple linear regression.Results In total, 46 respondents (84.8% males, aged 50–59 years) participated in this study. The average behavioral score was 153.72, with a standard deviation of 1.13. The average lifespan of RPADs was 5.33 years. The correlation analysis showed a moderate positive correlation between behavioral scores and RPAD lifespan (r = 0.463, p = 0.001). Multiple regression analysis indicated a significant association between behavioral scores and RPAD lifespan, with a coefficient B-value of 0.259 (p = 0.012).Conclusion Good RPAD maintenance behavior correlates with a longer RPAD lifespan. Socialization programs and instructions for RPAD care need enhancement to ensure optimal quality of life and performance among TNI soldiers.
Keywords: partial removable dentures; soldiers; lifespan; maintenance behavior; oral health